Severance Pay and Corporate Finance : Empirical Evidence from a Panel of Austrian and Italian Firms - Mirko Cardinale; Mike Orszag (Institute for the Study of Labor (IZA), 2004)
This paper examines the empirical link between severance pay and corporate finance. Severance pay is an economic debt of the employer and hence should be taken into account by the market in its assessments of risk. Using a hand collected dataset of accounting data from Italy and Austria we find there is only a limited relationship between severance pay and market risk indicators. This suggests that arguments that severance pay systems destroy corporate value may need to be reassessed.
Keywords: G39; J32; J65; 330; severance pay; corporate finance; Austrian employee benefits; Italian employee benefits; Abfindung; Finanzierung; Kreditrisiko; Schätzung; Österreich; Italien